Bildung enquanto formação estética no jovem Nietzsche - Cruz, Raimundo José Barros (2013)
This research investigates the concept of Bildung in the aesthetic formation in young Nietzsche s philosophy, taking the composition The Birth of Tragedy: Out of the Spirit of Music (1872) as the main target of investigation and interpretation. The issue of research that guides the investigation revolves around the possibility of viewing art as a questioning and unsettling dimension of modern rationality so as to favor subjective and inter-subjective experiences which, in an ethical-aesthetic orientation, challenge pedagogy to think up formative methods in contemporaneity. The research will be based upon the thesis that Bildung in young Nietzsche occurs in aesthetic formation under tragic orientation which, during the interpretation of existence as an aesthetic phenomenon, disconnects itself from the intended modern moral subject and founds an aesthetic subject who is capable of justifying his own existence. In the strict sense, Nietzschean critics focus on the whole modern pedagogical project which, following the tracks of the Aufklärung, has built a formative ideal whereupon educating for science and developing technical skills have become master guidelines for the West. This refers to the turnaround provoked by Nietzsche as he criticized science, politics, moral, religion, and education: the transition from the current utilitarian sense of education and the bourgeois formation, in his time, to the tragic sense of the formation theme. In this context, the Nietzschean aesthetic problem has inevitably attached itself to the problem of formation, in his time, indicating a peculiar path. This study starts from the recognition of the totally new constitution taken up by young Nietzsche in the rupture of interpretative tradition where the moral and rationality, by far, have always favored the veiling of the aesthetic dimension. The study will be divided in four parts. In the first chapter we will investigate the Nietzschean Bildung in the general context of debate about the formation in Germany, in the 19th century. We will focus on situating the research and our subject matter in the broad scope of debates about German Bildung, its several authors, settings and philosophical, educational, political, and social perspectives, in order to map the understanding of the Nietzschean aesthetics as a formation problem, which acquires its traits while criticizing the concepts of formation in his time. In the second chapter we will interpretively rebuild the aesthetic influences from Arthur Schopenhauer and Richard Wagner on young Nietzsche, as well as his choice to replace the problem of aesthetic formation for criticism to modern rationality. In the third chapter we will reflect mainly on Nietzschean aesthetic in The Birth of Tragedy, his tension between the Apollonian and Dionysian as well as the foundation of an aesthetic of the existence as a confirmation of life. Finally, in the fourth chapter, we will discuss the concept of Bildung in young Nietzsche as aesthetic formation by investigating such undertaking in moral criticism and in the need of life reinforcement which in the art world awakens to the importance of the relation between archaic Greece and the formative experience.